Appreciating diversity : is the doctrine of margin of appreciation as applied in the European Court of Human Rights relevant in the African human rights system? - Cistac, Gilles (University of Pretoria, 2006)
Prepared under the supervision of Prof. Gilles Cistac at the Faculty of Law, Universidade Eduardo Mondlane, Maputo, Mocambique